(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The theory of equivalence in translation studies, encompassing formal and dynamic approaches, serves as a foundational framework for bridging linguistic and cultural gaps. This article examines its application in the niche field of Japanese-Uzbek literary translation, where cultural disparities and structural differences pose unique challenges. Drawing on examples from translated works like Haruki Murakami’s A Wild Sheep Chase and Kobo Abe’s Woman in the Sand, it analyzes strategies such as substitution, paraphrasing, and cultural adaptation to achieve equivalence. The study highlights the tension between fidelity to the source text and naturalness in the target language, emphasizing the need for pragmatic and cultural competence. Findings underscore equivalence’s adaptability in non-Western translation pairs, contributing to cross-cultural literary exchange.